Controllable construction of pH-responsive hydrogel based on marine polysaccharides as oral delivery vehicle of tramadol. (October 2021) - Mao, S.; Guo, R.; Li, D.; Lv, C.; Sun, J.; Yang, D.; Meng, P.
Abstract: Because of the advantages of non-invasiveness and painlessness, oral administration can be applied to deliver opioid analgesics to interfere with chronic pain. However, the variability of pH in the gastrointestinal environment brings huge challenges for drug delivery. To establish an oral delivery vehicle that can controllably exist in the gastrointestinal environment. Tramadol was selected as a model drug, and the composite drug-loaded hydrogel based on sodium alginate and chitosan (Chi) was synthesized by a simple cross-linking method. Fourier transform infrared, X-ray diffraction, field emission scanning electron microscopy and other characterization methods have proved the formation of composite gel networks, which is caused by the strong interaction of functional groups between polysaccharides. Swelling and in vitro release experiments also show that the composite tramadol-loaded gel exhibits a relatively stable swelling and release behavior (about 73% of the release rate can be stabilized in the gastrointestinal delivery process). By adjusting the ratio of alginate and Chi, the responsive behavior of the hydrogel under different pH conditions can be further controlled. This study shows that alginate/Chi composite hydrogel has specific pH-responsive characteristics, which provides an effective solution for the design of controllable oral delivery analgesic carriers.